2008
DOI: 10.1002/bjs.6234
|View full text |Cite
|
Sign up to set email alerts
|

Flexible sigmoidoscopy and whole colonic imaging in the diagnosis of cancer in patients with colorectal symptoms

Abstract: Patients with iron deficiency anaemia or a mass require WCI. However, in patients with symptoms alone, FS detects 95 per cent of cancers, and the diagnostic yield of WCI after FS is very low. Alternative management strategies need to be developed to avoid unnecessary investigations in this low-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 18 publications
1
68
0
Order By: Relevance
“…In a large study involving 16,433 symptomatic cases who underwent flexible sigmoidoscopy over a 16 year period in a single colorectal unit in south of England, it was shown that the chance of missing a proximal lesion with this procedure is about 2.5% (Thompson et al, 2008). In West Africa about 50% of colorectal cancers are located in the rectum of which 78% are within reach of the examining finger, with another 20% in the sigmoid, descending and splenic flexure of the colon (Dakubo et al, 2010;Irabor and Adedeji, 2009;Naaeder and Archampong, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In a large study involving 16,433 symptomatic cases who underwent flexible sigmoidoscopy over a 16 year period in a single colorectal unit in south of England, it was shown that the chance of missing a proximal lesion with this procedure is about 2.5% (Thompson et al, 2008). In West Africa about 50% of colorectal cancers are located in the rectum of which 78% are within reach of the examining finger, with another 20% in the sigmoid, descending and splenic flexure of the colon (Dakubo et al, 2010;Irabor and Adedeji, 2009;Naaeder and Archampong, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal endoscopic screening has greatly improved the detection rates of early disease (Stages I and II disease) in the West, more so in whites than in blacks. 5 The stage of colorectal cancer at time of diagnosis reported in the US 34 Of the 321 patients with adenocarcinoma all except four had invasive tumour. The patients with carcinoma-insitu presented with rectal bleeding and had endoscopy which identified their tumours that were subsequently resected after histological confirmation of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data for these investigations were then collected by removing the 'primary care' filter from the search. The following papers were considered to inform the accuracy of the remaining investigations: Oono et al 101 for faecal immunochemical testing, Thompson et al 102 for flexible sigmoidoscopy, Pickhardt et al 103 (only sensitivity) and Halligan et al 104 for CTC, and Pickhardt et al 103 for colonoscopy.…”
Section: Diagnostic Accuracymentioning
confidence: 99%